A comparative study of issue and candidate orientation of voters in rural and urban barangays. - Azarraga, Josephine de Castro
Voting is the most important political activity, and for most Filipinos the only means of political participation, engaged in by citizens in a democratic society. Thus, it is important to examine the degree of importance given by voters towards issues as opposed to candidates' described as personal traits and achievements and their (the voters') particularistic interests' when they cast their votes. To locale, which is either rural or urban, may possibly show different degrees of these influences on the voters. This study, therefore, seeks to determine the level of issue and candidate orientations of voters in rural and urban barangays. The study also aims to compare the level of issue and candidate orientations of voters from rural and urban barangays., Given these objectives, a survey was conducted in the rural barangays of Bacauan, Indag-an and North Kirayan in Miagao and the urban barangays of San Pedro, Rizal and Rizal Pala-pala II in Iloilo City with a total of 100 respondents. A questionaire which contains issue and candidate orientation scales was used. These scales were designed to elicit the issue awareness and concern of the respondents when they chose their candidate for president in 1992 election as well as the respondents' attraction towards candidates when they voted. The findings of the study reveal that voters in rural barangays are moderately issue-oriented. The study also found a majority of the voters from urban barangays to be moderately issue oriented. Among rural voters, the level of candidate orientation was found to be moderate. Voters from urban barangays were found to have a moderate level of candidate orientation. Results of the study using the Mann-Whiney U test showed that voters from rural barangays were no less issue-oriented than those from urban barangays. Also, no difference was found in the level of candidate orientation of rural and urban voters. Results suggest that attitudes towards candidates and issue in national elections are not affected by the locale of the voter.